The Fourth International Workshop on Clinical Transplant Tolerance. Issue 1 (22nd July 2020) - Issa, Fadi; Strober, Samuel; Leventhal, Joseph R.; Kawai, Tatsuo; Kaufman, Dixon B.; Levitsky, Josh; Sykes, Megan; Mas, Valeria; Wood, Kathryn J.; Bridges, Nancy; Welniak, Lisbeth A.; Chandran, Sindhu; et al.
Abstract : The International Workshop on Clinical Transplant Tolerance is a biennial meeting that aims to provide an update on the progress of studies of immunosuppression minimization or withdrawal in solid organ transplantation. The Fourth International Workshop on Clinical Tolerance was held in Pittsburgh, Pennsylvania, September 5‐6, 2019. This report is a summary of presentations on the status of clinical trials designed to minimize or withdraw immunosuppressive drugs in kidney, liver, and lung transplantation without subsequent evidence of rejection. All protocols had in common the use of donor or recipient cell therapy combined with organ transplantation. The workshop also included presentations of mechanistic studies designed to improve understanding of the cellular and molecular basis of tolerance and to identify potential predictors/biomarkers of tolerance. Strategies to enhance the safety of hematopoietic cell transplantation and to improve patient selection/risk stratification for clinical trials were also discussed. Abstract : This report summarizes the status of trials designed to minimize or withdraw immunosuppressive drugs in kidney, liver, and lung transplantation.